Etyczne problemy sprawowania władzy w zarządzaniu przedsiębiorstwem - Pawlak, Zbigniew; Smoleń, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2008)
When power is exercised in the enterprise some ethical issues might occur with business ownership, personnel policy, working conditions etc. These issues and ways of addressing them were depicted and interpreted from the perspective of the Church’s social teachings included in papal encyclicals, viz.: Rerum novarum, Laborem exercens, Centesimus Annus. In the Church’s social teachings a number of principles were noticed that are favourable for the ethical corporate management including the principle of the primacy of work over capital, right to private ownership, right to establish professional associations, right to fair pay, right to fulfil religious obligations and having rest during holidays, a duty to support the weak and the needy (solidarity principle). The analysis of the social content of papal encyclicals showed two faces of power. On the one hand it is necessary and has positive effects (introduction of corporate governance, taking right decisions, prevention of theft and assets devastation etc.); on the other hand improper power exercise may lead to a number of undesirable effects (corruption, worker discrimination, thriftlessness etc.) The paper identifies also sources, forms and power exercising planes in the enterprise.